2002
DOI: 10.1021/ja012645k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Carbon Monoxide Complex of [NiFe]hydrogenase fromDesulfovibriovulgarisMiyazaki F:  Suggestion for the Initial Activation Site for Dihydrogen

Abstract: The carbon monoxide complex of [NiFe]hydrogenase from Desulfovibrio vulgaris Miyazaki F has been characterized by X-ray crystallography and absorption and resonance Raman spectroscopy. Nine crystal structures of the [NiFe]hydrogenase in the CO-bound and CO-liberated forms were determined at 1.2-1.4 A resolution. The exogenously added CO was assigned to be bound to the Ni atom at the Ni-Fe active site. The CO was not replaced with H(2) in the dark at 100 K, but was liberated by illumination with a strong white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
240
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(253 citation statements)
references
References 55 publications
(113 reference statements)
13
240
0
Order By: Relevance
“…On the other hand, some discrepancies are found in the number of thiolates between metals (three for 3 and two for hydrogenase) and the diatomic ligands on iron (FeðCOÞ 3 for 3 and FeðCOÞðCNÞ 2 for hydrogenase). Furthermore, the Ni-Fe distance in 3 (3.17 Å) is substantially longer than those in the protein (2.61-2.62 Å) (42). Perhaps the oxidation states of Fe and/or Ni of 3 are different from those of the structurally characterized CO-inhibited form of [NiFe] hydrogenase.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, some discrepancies are found in the number of thiolates between metals (three for 3 and two for hydrogenase) and the diatomic ligands on iron (FeðCOÞ 3 for 3 and FeðCOÞðCNÞ 2 for hydrogenase). Furthermore, the Ni-Fe distance in 3 (3.17 Å) is substantially longer than those in the protein (2.61-2.62 Å) (42). Perhaps the oxidation states of Fe and/or Ni of 3 are different from those of the structurally characterized CO-inhibited form of [NiFe] hydrogenase.…”
Section: Discussionmentioning
confidence: 94%
“…According to a crystallographic analysis of the CO-inhibited form of the [NiFe] hydrogenase obtained from Desulfovibrio vulgaris Miyazaki F (D. v. Miyazaki F), a CO molecule is coordinated at the nickel center (42). It has been suggested that this nickel-bound CO can be liberated and the catalytic activity recovered, upon flushing with a stream of N 2 (43), or by white-light irradiation at 20 K (44 (45)(46)(47).…”
mentioning
confidence: 99%
“…2.71 Å for H 2 , calculated from gas viscosities) (20); consequently, CO must also have access, and the fact that it does not inhibit suggests an inability to form a metal-CO bond. According to structural and spectroscopic studies carried out on the standard [NiFe] hydrogenase from D. vulgaris (Miyazaki F), the exogenous (inhibitory) CO molecule binds to the Ni atom (21). It is thus important to know how typical is the active site of Re MBH.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, comparative crystallography showed that CO and O 2 inhibited [NiFe] hydrogenases show additional diatomic electron density at the open fifth coordination site at Ni. 138 In the oxidized ''unready'' state of the enzyme, an additional elongated electron density was observed at the bridging ligand ''X'', suggesting it to be a hydroperoxide OOH À . 128 It is suggested that the peroxo bridging ligand causes the enzyme to be ''locked'' in the unready state which can be reactivated only very slowly.…”
Section: 132133mentioning
confidence: 99%